2018
DOI: 10.5935/2595-0118.20180029
|View full text |Cite
|
Sign up to set email alerts
|

The most uncomfortable chronic pain in primary school teachers: differential between different body regions

Abstract: BACKGROUND AND OBJECTIVES: Chronic pain is a complex and multifactorial event. Very few research compare chronic pain according to the body region in teachers, a population with demanding workloads. The objective was to characterize the most uncomfortable chronic pain, reported by teachers, according to the body region. METHODS: A cross-sectional study conducted from 2012 to 2013 with K-12 teachers from the 20 largest state schools in Londrina (PR). Chronic pain (≥6-month duration) and the one that bothered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
6
0
7
Order By: Relevance
“…In primary care, for example, chronic pain is one of the main reasons for seeking care [2]. The body regions commonly affected by CMP are the back [3,4] and upper and lower limbs [5,6]. Some health conditions often associated with CMP are tension, fatigue [7], depression and low quality of life scores [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In primary care, for example, chronic pain is one of the main reasons for seeking care [2]. The body regions commonly affected by CMP are the back [3,4] and upper and lower limbs [5,6]. Some health conditions often associated with CMP are tension, fatigue [7], depression and low quality of life scores [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of back pain was higher among teachers who reported increased body weight during the pandemic. Weight gain can result in obesity, and the literature highlights a bidirectional relationship between obesity and complaints of musculoskeletal pain (Gabani et al 2018 ; Walsh et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significant relationship between irregular sleeping pattern and MSDs among teachers is corroborated in a study with state school teachers in Londrina, state of Paraná, Brazil, which revealed that pains in ULs and LLs were factors that hindered workers’ sleep. 29 It is worth highlighting that this relationship may have a bimodal nature, since MSDs may have an influence on sleep and poor sleep quality may lead to the onset of MSDs. 30 …”
Section: Discussionmentioning
confidence: 99%